Supply Chain Management Strategies of the Private Residential Construction Sector in South Africa - Khoza, G.; Govender, Krishna Kistan (The Journal of Accounting and Management, 2024)
The aim of the study was to critically evaluate the supply chain management (SCM) strategies and challenges in the private residential construction sector in South Africa. A quantitative approach was used to survey 320 private residential construction companies registered with the National Homebuilders Registration Council (NHBRC) within the Gauteng province. The data from 250 questionnaires returned were analysed using SPSS (Versions 23) and Smart PLS. It became evident that the SCM challenges included a lack of trust between the supplier and the organization; a lack of adoption of the SCM system; a lack of a sufficiently skilled SCM workforce; and poor implementation of contract management. It was ascertained that there is a significant positive relationship between the performance of the private residential construction sector in South Africa and the SCM strategies and processes. Strategies are proposed to enhance performance.